The effects of R&D intensity and internationalization on the performance of non-high-tech SMEs. (February 2018) - Booltink, Lucas WA; Saka-Helmhout, Ayse
Research and Development (R&D) investment is seen as a fundamental driver of high-tech small and medium-sized (SME) firm performance. However, the same driver may be constraining growth among non-high-tech SMEs as it increases the level of risk faced by such firms. We challenge this argument by examining the relationship between R&D intensity and performance among non-high-tech SMEs. While the size of R&D investments is, by definition, limited in the non-high-tech sector, our study shows that such investments are important for non-high-tech firms. There is, however, an inverted U-shaped relationship between R&D intensity and performance among non-high-tech SMEs. Furthermore, increased internationalization leads non-high-tech SMEs to exploit their R&D investment more effectively to enhance firm performance, provided that R&D investment levels exceed a critical threshold.